PENGEMBANGAN MEDIA PUZZLE MENYUSUN BAIT PANTUN KELAS V SD NEGERI 98 PALEMBANG - Wiki Tegu Kurnia; Liza Murniviyanti; Aldora Pratama (STKIP Subang, 2023)
ABSTRAC his study aims to develop valid puzzle media on the material for composing verses and to develop practical puzzle media for the material for composing verses for class V SD Negeri 98 Palembang. The type of research used by researchers is R&D. The type of development used is ADDIE (Analysis, Design, Development, Implementation and evaluation) . The population and sample of this study are the population of class V participants at SD Negeri 98 Palembang totaling 10 people. The results of research on puzzle media products composing verse rhymes for class V SD. These products are made using styrofoam materials of various colors. The advantages and results of the development of puzzle media in composing interesting rhyme verses and motivating students in the process of learning activities because they have interesting writing and numbers that are adapted to the ability of students to train concentration. The expert assessment shows that the media puzzle composes verses with a percentage of 72% validators, media experts and a percentage of 64% material experts. With this, it can be concluded that the development of puzzle media composing rhyme verses for class V SD is included in the valid category. And the results of student responses obtained a percentage of 88% in the one to one trial and a percentage of 87.7% in the small group trial. it can be concluded that the practicality of puzzle media in composing bat rhymes in fifth grade elementary school learning is included in the very practical cat Keywords: Media Puzzle, Composing Pantun, and Indonesian ABSTRAK Penelitian ini bertujuan untuk mengembangkan media puzzle yang valid pada materi menyusun bait pantun dan mengembangkan media puzzle yang praktis pada materi menyusun bait pantun kelas V SD Negeri 98 Palembang.. Jenis penlitian yang digunakan oleh peneliti adalh R&D jenis pengembangan yang dignakan adalah ADDIE (Analisys, Desain, Development, Implementasi dan evaluasi) . Populasi dan sampel penelitian ini yaitu populasi peserta kelas V SD Negeri 98 Palembang berjumlah 10 orang. Hasil penelitian produk media puzzle menyusun bait pantun kelas V SD. Produk tersebut dibuat deengan menggunakan bahan styrofoam yang beraneka warna. Keunggulan dan hasil pengembangan media puzzle menyusun bait pantun menarik dan memotivasi siswa dalam proses kegiatan pembelajaran karena memiliki tulisan dan angaka yang menarik yang disesuaikan dengan kemampuan peserta didik dalam melatih konsentrasi. Penilaiam para ahli menunjukan baliwa media puzzle menyusun bait pantun dengan persentase sebesar 72% validator ahli media dana persentase sebesar 64% ahli materi. Dengan denikian dapat disimpulkan bahwa pengembangan media puzzle menyusun bait pantun kelas V SD termasuk dalam kategori valid. Dan hasil respon siswa diperoleh persentase sebaesar sebesar 88% pada uji coba one to one dan persentase 87,7% pada uji coba small group Dengan demikian. dapat disimpulkan bahwa kepraktisan media puzzle menyusun bait pantun pada pembelajaran kelas V Sekolah Dasar termasuk dalam kategon sangat praktis. Kata Kunci : Media Puzzle, Menyusun Bait Pantun, dan Bahasa Indonesia